Pengaruh Testimoni Terhadap Keputusan Pembelian di Tiktok Shop - Siti Az zahra Br Batu Bara; Devi Trinita; Nurmala Hidayati; Yenni Samri Juliati Nst (Pusat Riset dan Inovasi Nasional, 2025)
This research analyzes the influence of testimonials on purchasing decisions at the Tiktok Shop using qualitative methods through interviews with 30 respondents. It can be concluded that testimonials play an important role in influencing purchasing decisions. Respondents tend to choose testimonials that are informative, descriptive and do not give the impression of exaggerating, the time spent also influences purchasing decisions. The results of this research confirm that authentic and genuine testimonials can be used as an effective marketing tool to attract attention and increase buyers' trust in a product.